Konsep Toleransi Beragama Dalam Tafsir Al-Qur’an Tematik Karya Tim Departemen Agama Republik Indonesia - Muhamad Ridho Dinata (UIN Sunan Kalijaga Yogyakarta, 2012)
In a decade of post-reformation era, the religious life has been nuanced with the vast existence of radical-fundamental movements that underscore the non-compromised mode of action and tend to legalize violence pursuing their aims in Indonesia. At the same time, it is urgent to note the release of The Thematic Exegesis (Tafsir) of Al-Qur’an: The Inter-religious Relationship as the implementation of RPJMN 2004-2009 by the Ministry of Religious affairs the Republic of Indonesia. The issue of the exegesis serves as the benchmark of various Tafsir of either in a too-literal or a too-liberal one appeared in Indonesia. The issue is then the relationship between the condition of religious life in Indonesia and The Thematic Exegesis of AlQur’an: The Inter-religious Relationship as the government type of Tafsir.This research uses a critical discourse analysis in that it implements Teun A. van Dijk’s model of discourse analysis focused on three dimensional constructions of discourse: text, social cognition, and social context. To sum up, the concepts of religious tolerance offered in the exegesis are the principles of religious freedom, the tolerance of religious other, and the harmonious principle. Those three concepts of religious tolerance are a government version as it is imbued in the Exegesis produced by the government. This underlines the relationship of the Exegesis as a product of knowledge and power.